Protein Surface and Core Dynamics Show Concerted Hydration‐Dependent Activation1. Issue 2 (14th November 2012) - Wood, Kathleen; Gallat, François‐Xavier; Otten, Renee; van Heel, Auke J.; Lethier, Mathilde; van Eijck, Lambert; Moulin, Martine; Haertlein, Michael; Weik, Martin; Mulder, Frans A. A.
<x xml:space="preserve">Abstract</x> By specifically labeling leucine/valine methyl groups and lysine side chains "inside" and "outside" dynamics of proteins on the nanosecond timescale are compared using neutron scattering (see picture). Surprisingly, both groups display similar dynamics as a function of temperature, and the buried hydrophobic core is sensitive to hydration and undergoes a dynamical transition.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>